1944 Water Treaty Between Mexico and the United States: Present Situation and Future Potential - Sánchez, Anabel (Frontera Norte, 2017)
Historically and culturally, water has always been considered to be a critical issue in Mexico- USA agenda. Along the 3 140-km border between Mexico and the United States, there is intense competition over the adequate availability of water. Water uses in urban border areas have continued to increase exponentially due to steadily increasing levels of population growth. Rapid industrialisation and urbanisation have resulted in more intensive patterns of water consumption and use. Agricultural water demands continue to be high. Mexico and the United States have established institutions and agreements to manage and protect rivers in the border region. The Treaty between Mexico and the United States for the Utilisation of Waters of the Colorado and Tijuana Rivers and of the Rio Grande was signed in 1944. With the turn of the century, the growing urban centers along the Rio Grande (Rio Bravo), where the river becomes the international boundary, started increasingly to depend on groundwater. This situation was not specifically addressed in the 1944 Treaty, especially as groundwater use at that time was not so significant. RESUMEN El manejo y distribución del agua en la frontera ha sido, históricamente, uno de los temas controvertibles en la relación México-Estados Unidos. Desde 1945 a la fecha, la población se ha cuadruplicado en esta región fronteriza de más de 2 000 millas (más de 3 000 kilómetros). Debido a que esta zona presenta un escaso nivel de precipitación pluvial, con el paso de los años, los centros urbanos a lo largo de esta franja fronteriza han tenido que depender del río Bravo y de depósitos subterráneos para poder satisfacer la creciente demanda de agua. Esta situación ha rebasado las disposiciones establecidas en el Tratado Internacional de Límites y Aguas entre México y Estados Unidos, instrumento que desde 1944 se ha encargado de la utilización de las aguas del río Colorado, río Tijuana y río Bravo en la frontera entre estos dos países. La actual demanda de agua en esta zona y las condiciones poco claras establecidas por el tratado en términos de sequía extrema han provocado que el manejo y la sobreexplotación de los acuíferos se hayan convertido en punto focal de las discusión binacional que conmina a reflexionar acerca de los términos del tratado de 1944.